Upaya Penanggulangan Toxic Word pada Remaja di Kelurahan Kasongan Baru - Nor Kartila; Alfi Khaerah; Titi Khairunnisa; Novita Rama Liana; Julia Arsa; Jelita Jelita; Muhamad Khoeri; Aldi Feriyanto (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2024)
As an effort to address the issue of toxic words among adolescents in Kelurahan Kasongan Baru, education is essential. Therefore, the socialization of toxic words is highly relevant. This socialization aims to provide an understanding to adolescents about the negative impacts of using toxic words. The activity was held at SMPN 1 Katingan Hilir as a form of community service, targeting students aged 11 to 13 years. Before the socialization, a pre-test questionnaire was distributed to assess the students' understanding of toxic words. The survey results indicated that 92.1% of respondents were aware of the term, but only a few understood its negative consequences. After the educational intervention through socialization, the post-test results showed that 90% of students understood the concept of toxic words, with 78% committing not to use them again. Therefore, this socialization is considered successful due to the increase in students' understanding. Although progress has been made, challenges in behavioral change remain, necessitating ongoing educational programs. The service team recommends collaboration with the school and professionals to create a more positive environment that supports students' development as the future generation of the nation.